Perception And Knowledge Of Patients Towards CT Scan - Sehrawat, Harshit; Chandra, Sourabh; Soni (PT), Abhishek; Chawla, Sachin; Negi, Aditya (Journal of Neonatal Surgery, 2025)
Computed Tomography (CT) scans are vital diagnostic tools, yet patient awareness and perceptions regarding their use and associated radiation risks remain underexplored. This crosssectional study aimed to assess patient knowledge, perception, and experience of CT scans at the Radiology Department of Maharishi Markandeshwar Institute of Medical Sciences and Research (MMIMSR) from December 2021 to April 2022. A retrospective, qualitative survey involving 50 patients was conducted using a questionnaire with open- and close-ended questions. Results revealed that 66% of patients reported no explanation from radiographers about the scan, 86% were unaware of the type of rays involved, and 82% lacked knowledge of radiation risks. Despite this, 46% reported a good post-examination experience, though 62% were dissatisfied with examination room cleanliness. These findings highlight significant gaps in patient education and communication, underscoring the need for improved radiographer-patient interactions and radiation risk awareness to enhance patient-centered care.